Development Aspects of Post-Merger Islamic Banks: A Systematic Literature Review - Ainul Fatha Isman; Ega Rusanti; Armin Rusli Makatita (Perbanas Journal of Islamic Economics and Business, 2023)
Banking plays the role of a financial intermediary and is also considered to have a central position in the economy. The strategy pursued by Islamic banking is to merge with the aim of improving various aspects of it. This study aims to analyze the important aspects of Islamic banking, especially post-merger. This study uses qualitative research with the A Systematic Literature Review (SLR) approach. Data collection was carried out by surfing the internet from Google Scholars and Emerald. The research data population is journals with a focus on aspects of development in post-merger Islamic banking as many as 25 indexed journals from various publishers or journal publishers. According to the findings of this study by a systematic literature review show that several aspects that need to be improved after the merger are Profitability, Shariah Compliance, Technology, Human Resources, Management, Business and Marketing, and Efficiency. Humam resources aspect is a dominant aspect in building a positive image of sharia banking has escaped his attention after merger. This research implies to shariah banking for know the urgency of increasing post-merger and to be improve several aspects for development the Islamic bank in Indonesia.